VITAMIN D REGULATION OF BONE METABOLISM - E. A. Maylyan; N. A. Rheznichenko; D. E. Maylyan (Медицинский вестник Юга России, 2017)
The main vitamin D (1,25(OH)2D) function lies in maintaining of calcium and phosphates normal concentrations in a blood plasma that is necessary for adequate bone tissue mineralization and skillet formation. Now there’s no doubt that vitamin D immediately participates in the bone tissue metabolism, directly influencing through VDR receptors located on cells: chondrocytes, osteoblasts, osteocytes and osteoclasts. At that, mechanisms of calcium and phosphorus intestinal absorption stimulation and immediate vitamin D influence on bone cells are significant and complementary in the full-fledged bone tissue metabolism regulation process.